Antimicrobial sensitivity in urinary tract obstruction due to calculus: a study of 50 cases - Tandel, Prabhubhai R.; Patel, Himanshu R.; Patel, Kiran U. (International Surgery Journal, 2018)
Background: The urinary tract obstruction occurs due to several causes. one of the most important cause of obstruction is urinary calculus. urinary calculi are the third most common affliction of the urinary tract exceeded only by urinary tract infection and pathology of prostate. Improvement of the medical facility and increased health consciousness has resulted in more patients presenting with early urinary tract obstruction due stone. Methods: This is prospective study. It was conducted from July 2017 to August 2018 at GMERS medical college Valsad. A Study of 50 cases was carried out, after thorough clinical examination and necessary investigations, patients were subjected to x ray KUB, ultrasonography, intravenous pyelography. The samples were cultured & Antimicrobial sensitivity determined. Results: Escherichia coli is the commonest urinary pathogen causing 60 -90 % of infection, but in this study 72% of patient came infected with Escherichia coli 16% came infected with Klebsiella. Infection of anterior urinary tract (Urethritis) is mainly caused by N. Gonrrhoeae, staphylococci and chlamydia. Gentamicin is found to be most effective drug (78% sensitivity) in present series this is followed by Gatifloxacin (60% sensitivity), Septran (36% sensitivity) & Cefotaxime (34% sensitivity). Conclusions: It is concluded that most of the urinary tract infections in human are caused by Escherichia coli with more sensitivity to Gentamicin.